Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1039/d2ee03185j
|View full text |Cite
|
Sign up to set email alerts
|

A high-entropy atomic environment converts inactive to active sites for electrocatalysis

Abstract: To understand the mechanism of the reaction catalyzed by high-entropy-alloy (HEA) electrocatalysts, it has become increasingly crucial to investigate the chemical nature of the adsorbed intermediate species on the metal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(70 citation statements)
references
References 50 publications
1
57
0
Order By: Relevance
“…37 Also, studies have revealed that the active sites in HEA catalysts are the most electronegative among the ve elements. [38][39][40][41] On the other hand, HEMS/P materials are still in their early stages as new electrocatalysts, with recent research primarily focusing on synthesis methods and component selection. The complex nature of the HEMS/P system, which consists of different transition metals with varying oxidation states, makes understanding the role of various active sites in electrode reactions a challenging task.…”
Section: Summary and Future Directionmentioning
confidence: 99%
“…37 Also, studies have revealed that the active sites in HEA catalysts are the most electronegative among the ve elements. [38][39][40][41] On the other hand, HEMS/P materials are still in their early stages as new electrocatalysts, with recent research primarily focusing on synthesis methods and component selection. The complex nature of the HEMS/P system, which consists of different transition metals with varying oxidation states, makes understanding the role of various active sites in electrode reactions a challenging task.…”
Section: Summary and Future Directionmentioning
confidence: 99%
“…In this respect, low-cost transition metal-based oxides, hydroxides, high entropy alloys, layered double hydroxides (LDH), and chalcogenides were intensively studied as efficient OER electrocatalysts. [16][17][18][19][20][21][22][23][24][25][26][27] Among them, CoFe-LDH with a brucite-like crystal structure is considered to be a precursor for many high performance electrocatalysts. [28][29][30][31][32][33][34] Several approaches including heterostructural engineering, connement of intermediate in nanogrime channel, and creating a multifunctional surface at the interface have been used to minimize the kinetic barriers and breakage of the scaling relation.…”
Section: Introductionmentioning
confidence: 99%
“…Single-atom catalysts (SACs) have sparked promising interest in the fields of energy conversion, environmental issues, and material sciences owing to their remarkable properties, including high activity, high selectivity, and 100% atom utilization compared with their bulk counterparts. SACs have been considered as promising electrocatalysts for water splitting, oxygen reduction reaction (ORR), CO 2 electroreduction reactions (CO 2 RR), and nitrogen reduction reaction (NRR). , Considerable efforts have been devoted to develop effective strategies for preparing SACs, including chemical etching, chemical impregnation, electrochemical reconstruction, pyrolysis, and defect trapping. Owing to their high surface free energy, SACs require supports such as metal oxides and heteroatom (N, O, S, and P)-doped carbon materials to anchor free atoms to prevent their aggregation into particles, known as thermal deactivation or sintering, which may decrease their catalytic performance. However, recent studies have reported that N-doped carbon (NC)-supported single-atom Cu 2+ can be transformed into Cu 0 small clusters or nanoparticles (NPs) under a certain range of negative electrode potentials from −0.4 V to −1.0 V vs reversible hydrogen electrode (RHE), resulting in the structural transformation of SAs during CO 2 RR . The aforementioned transformation of NC-supported SA Cu 2+ can be attributed to the lack of appropriate interactions between the SA and NC under low applied potentials (<−0.5 V), resulting in the instability and aggregation of active atoms.…”
Section: Introductionmentioning
confidence: 99%